ASSESSMENT OF GOAT MICRO-CREDIT PROJECT AS A STRATEGY OF POVERTY REDUCTION AMONG RURAL WOMEN IN SELECTED LOCAL GOVERNMENT AREAS OF JIGAWA STATE, NIGERIA - Dandawo, H.; Bose, A. A.; Jibril, S. A. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study assessed Goat Micro-Credit Project as a strategy of poverty reduction among rural women in selected Local Government Areas of Jigawa State, Nigeria. Multistage sampling technique was used in selecting 180 rural women were selected. Primary data were obtained using structured questionnaires and analyzed using both descriptive and inferential statistics. The result shows that majority (76.7%, 63.3% and 58.3%) of the respondents were within the ages of 30-59 years, married and had a household size of 2-7 persons respectively, with a mean age of 42 years and 7 persons, respectively. The results also reveal that less than half (48%) of the respondents had no formal education and majority (63.3%) of the respondents were not members of cooperatives. The result also shows that respondents agree that goat micro-credit increases income (=4.9), good livelihood (=4.1) and access to credit (=4.6) among others. On the other hand marital status, household size were positive and significant (P<0.05) factors influencing credit repayment, while age was negative and significant (P<0.05) factor influencing credit repayment. The major constraints faced by the respondents were inadequate extension agents, working capital and high cost of medication and were ranked 1st, 2nd and 3rd respectively. The study concludes that respondents’ livelihood and standard of living were improved by the project and that socio-economic characteristics of the respondents had significant influence on their repayment ability. The findings recommend that government should employ and deploy more extension agents, respondents should form and actively participate in cooperatives so as to increase their access to capital.